2012
DOI: 10.1002/anie.201202936
|View full text |Cite
|
Sign up to set email alerts
|

The Dehydrogenation of Alcohols through a Concerted Bimetallic Mechanism Involving an Amido‐Bridged Diiridium Complex

Abstract: Interest in catalytic functionalization of ammonia into higher-value nitrogen-containing products constitutes today a hot topic. [1] However, productive participation of ammonia as substrate in homogeneous catalysis is normally hampered by the intrinsic high strength of the N-H bond, very difficult to activate by metal centres. [2] Therefore, it is convenient to find alternative ways to achieve the formation of [M-NH 2 ] species directly from ammonia as a premise to accomplish its subsequent functionalizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 71 publications
0
24
0
Order By: Relevance
“…Catalytic activity of the cyclooctadiene complexes 1 and 2 in the transfer hydrogenation of acetophenone : In a preliminary communication we reported that complex 2 , at room temperature and in absence of any base, was active as homogeneous catalysts for the transfer hydrogenation of acetophenone to 1‐phenylethanol by using i PrOH as hydrogen donor. Under such mild conditions a bimetallic mechanism that allows a concerted net hydrogen transfer through a proposed eight‐membered dimetallacycle was proposed 25. However, the catalytic activity was relatively low and, in the absence of acetophenone, or when its concentration was substantially decreased, the formation of a stable imido cluster of the formula [Ir 3 (cod) 3 (μ 2 ‐H)(μ 3 ‐NH) 2 ] was observed.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Catalytic activity of the cyclooctadiene complexes 1 and 2 in the transfer hydrogenation of acetophenone : In a preliminary communication we reported that complex 2 , at room temperature and in absence of any base, was active as homogeneous catalysts for the transfer hydrogenation of acetophenone to 1‐phenylethanol by using i PrOH as hydrogen donor. Under such mild conditions a bimetallic mechanism that allows a concerted net hydrogen transfer through a proposed eight‐membered dimetallacycle was proposed 25. However, the catalytic activity was relatively low and, in the absence of acetophenone, or when its concentration was substantially decreased, the formation of a stable imido cluster of the formula [Ir 3 (cod) 3 (μ 2 ‐H)(μ 3 ‐NH) 2 ] was observed.…”
Section: Resultsmentioning
confidence: 99%
“…Under such mild conditions a bimetallic mechanism that allows a concerted net hydrogen transfer through a proposed eight-membered dimetallacycle was proposed. [25] However, the catalytic activity was relatively low and, in the absence of acetophenone, or when its concentration was substantially decreased, the formation of a stable imido cluster of the formula [Ir 3 A C H T U N G T R E N N U N G (cod) 3 A C H T U N G T R E N N U N G (m 2 -H)A C H T U N G T R E N N U N G (m 3 -NH) 2 ] was observed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, it has been reported recently a special example of the metal-ligand bifunctional mechanism involved with a dinuclear amido bridged iridium(I) complex )(cod)} 2 ], in which a concerted cooperation of the metals and the amido bridges is essential for the hydrogen transfer of isopropanol to acetophenone to occur. [12] …”
Section: Introductionmentioning
confidence: 97%